Modifying the Technological Properties and the Release of Cocoa Compounds of Active Gliadin Films by Increasing the Temperature of Processing - Rojas-Sepulveda, A (Institution of Chemical Engineers, 2025)
The search for bio-based polymers from renewable sources and compostable nature is undoubtedly a focus of interest and need in the area of plastics and mainly for food packaging. Gliadins, proteins found in wheat gluten, are an interesting and sustainable alternative because they are biodegradable, come from a renewable source and have interesting properties as gas barrier, although some technological properties need to be improved in order to broaden their applications. In this work, gliadin bioresin films were processed with water- and lipid-soluble cocoa extracts at 5 and 10 % respect polymer weight by thermo-compression at 90 and 130 °C in order to study both the effect of the type of extract, their concentrations and the processing temperature on the physical and functional properties of the active systems. Undoubtedly, the main condition that positively affected the properties of the resulting active films was the thermo-compression at 130 °C, since it allowed a better miscibility between the active compounds and the biopolymeric chains of the gliadins, and produced a certain crosslinking between disulphide/sulfhydryl groups and polyphenol-protein bonds that resulted in their water resistance. The reduction of weight loss in water achieved values up to 60 %, while in ethanol 95 %, the improvement in resistance was not significant. The mechanical properties of active gliadin films were also highly affected principally when processed at 130 ºC; the elastic modulus decreased while the elongation at break values increased up to values between 113 % and 150 %. The water vapor permeability was greatly reduced from 4.22 to 2.4 × 1014 Kg m/m2 s Pa for active gliadin film containing 10 % lipid soluble cocoa extract. The release of cocoa compounds was totally dependent on the type of the extract and the food simulant. The general conclusion was that by modifying the active compounds and the processing temperature, gliadin films with different technological and antioxidant properties were achieved. © 2025 Institution of Chemical Engineers (IChemE)